Ceramic combinatorial syntheses exploring the chemical diversity of metal oxides. (December 2016) - Iranmanesh, M.; Hulliger, J.
Abstract: A ceramic combinatorial method to investigate the phase space of e.g. metal oxides by a single sample is reviewed along with its application to cuprate superconductors. The main idea behind this method is to use a large number N of starting materials (micrometer size grains) to generate local reaction centers producing possible compounds at the reaction temperature. Mathematical calculations using also empirical data on the occurrence of compounds in phase systems allow to conclude that in 1 cm 3 of a sample, there are enough grains to populate all local reaction centers in order to obtain in principle what the N starting materials can produce. A variety of characterization technics have been applied to such libraries to identify e.g. cuprate superconductors. Finally the success of the concept will depend on analytical tools allowing for a simultaneous analysis of the composition and physical properties. Here, we have applied for the first time scanning SQUID microscopy to reveal local superconductivity in inhomogeneous ceramic samples.